Consolidated bioethanol production using Trichoderma asperellum B1581 - Mohamed Ghazali, Mona Fatin Syazwanee; Mustafa, Muskhazli; Mohd Zainudin, Nur Ain Izzati; Abd Aziz, Nor Azwady (The Deanship of Scientific Research , The Hashemite University, Jordan, 2022)
Consolidated bioprocessing (CBP) is an alternative commercial process that combines all essential processes in a single bioreactor for the conversion of lignocellulosic biomass into ethanol. The challenge in the development of CBP is to find microorganisms with crucial properties for the utilisation of lignocellulosic materials to produce bioethanol. Also, it can be difficult to determine the optimal culture conditions for all processes to occur simultaneously. Therefore, this study focused on the potential of Trichoderma asperellum B1581 to produce ethanol and optimised the physicochemical parameters required for paddy straw waste conversion via CBP. Six parameters (days of saccharification, saccharification temperature (°C), days of fermentation, fermentation temperature (°C), medium level (%, v/v), and substrates loading (%, w/v)) were optimised in one-factor-at-a-time (OFAT) analysis via Response Surface Methodology (RSM). The numerical optimisation was statistically validated by comparing the volume of ethanol produced to the volume predicted by the RSM. T. asperellum B1581 produced 0.94 g/L bioethanol in CBP and is a more convenient, manageable and cost-effective process as all the crucial steps were performed by only one organism.